A Cautionary Tale: How Children's Books (Mis)Teach Shapes. Issue 4 (19th May 2017) - Nurnberger-Haag, Julie
ABSTRACT: Research Findings : Children's conceptions of shapes, including misconceptions, are quite robust by 6 years old and persist into adulthood, so it is important to inspect early sources of these conceptions. This study aimed to uncover whether children's books about shapes could be a source of inaccurate initial learning that remains with many adults in spite of school instruction. Thus, the study investigated the content of trade books to identify (a) 2-dimensional and 3-dimensional shapes portrayed, (b) reasoning level used, (c) explicitly accurate and inaccurate information conveyed, and (d) implicit inaccuracies conveyed. This content analysis of 66 shape books found that books portrayed a limited range of shapes in ways that encouraged low-level reasoning. A total of 76% of books had at least 1 explicit inaccuracy of 2-dimensional shapes. Explicit and implicit inaccuracies throughout the sample were consistent with common child and adult difficulties with 2-dimensional shapes. Practice or Policy : This study provides insights into possible sources of shape conceptions. Such knowledge suggests instructional implications and future research about ways in which teachers, librarians, parents, and other caregivers might better select and use trade books to facilitate more accurate shape concepts for young children that may have long-lasting influence.